دراسة تحليلية لواجهات المباني المعمارية - ودح, هاني هاشم (Latakia University Journal -Engineering Sciences Series, 2019)
المبنى كائن حي في بنيته، وكتلة من الأحاسيس والشعور تعكسها واجهاته. إذ يمكننا التعبير عن شيء من خلال إلقاء نظرة أولية فنقوم بوصفه ( شكله، لونه، واستخدامه... الخ ) وكل هذا بشكل أولي. وهناك مقولة تقول ( إن المكتوب يقرأ من عنوانه ) وعنوان المبنى واجهاته فهل يمكننا قراءة التعبير عن مكنوناته الداخلية من خلال هذه الواجهات. تهدف هذه الدراسة إلى معرفة ما يلي: 1 – كيفية تعبير واجهات المباني وشكل المبنى الخارجي عن وظيفته الداخلية من الناحية العلمية والأكاديمية 2 – إيجاد تصنيف لنماذج هذه الواجهات. Metaphorically speaking, a building is much like a human being in its structure full of different kinds of feelings and emotions which are reflected through its elevations. To depict a thing we first cast look on it then describe it (shape, colour, uses, etc) on a primarily basis. This paper shows that elevation of a building reflect its internal composition it does so by answering the following: 1. How elevations and exterior shape of a building can reflect its internal function academically and scientifically? 2. To find out a classification for the types of elevations.